(untitled) (Nonconventional Technologies Review, 2015)
The paper deals with technological performances increase at electrical discharge machining aided by ultrasonic longitudinal vibrations of electrode-tool (EDM+US), in terms of machining rate and machined surface roughness. Some experimental data are presented in relation with finite element modelling of EDM+US material removal process. The machining rate could be increased by growing the probability to overlap the pulse time on cumulative microjets stage (CMS) – the effect of ultrasonically induced cavitation in the frontal gap. The surface roughness could be decreased through optimization of a key-parameter of working mode, the consumed power on ultrasonic chain. All these technological improvement with market impact on EDM users segment, very sensitive to cost level, are feasible if the organization applying this hybrid technology (EDM+US) valorizes the connected intangible assets, operable through some main competencies, technology, supplying, marketing, innovation, quality assurance, continuous costs decrease provided by accumulated know-how and patents series in EDM field.